O cárcere na adolescência: ressonâncias de uma trajetória - Vale, Juliana Maria Batistuta Teixeira (2009)
This study aims to understand some of the multiple meanings of life trajectories of adolescents who have committed an act of infraction and faced prison. A transdisciplinary approach was used as a theoretical reference in order to enhance the understanding of the subject, bringing together different professional formation processes. This qualitative research came from my experience as a social worker in the monitoring of socio-educational measures applied to adolescent offenders. During the exploratory phase, resources pertinent to the ethnographic method were used to access the survey. For this reason, the investigation was performed taking as a basis the records of a field diary, which registered the extracts of a group of psychosocial care to adolescents who had left the juvenile prison. The reports of their memories and feelings in detention led me to revisit the institution, which was in the process of closing down, taking photographic registers of the area. The traces of the adolescents were in the drawings and sayings that were on the walls of the institution in ruins. After completing the socio-cultural contextualization of the prison in adolescence, a case study was used as a way to learn from life trajectory of adolescents. This step has been split between the analysis of documents of the institution that assisted the family of the studied case with the purpose of presenting the familiar scenario permeated by different forms of social and domestic violence. Later interviews with the central character in the story were also made. Interpretations of the information were carried out by the psychoanalytic method of analysis. It was understood that adolescents in conflict with the law and at risk have experienced various institutional interventions which are often powerless and contribute to morbid and unhealthy paths in life.